Enhanced Efficacy of Combinations of Pexiganan with Colistin Versus Acinetobacter Baumannii in Experimental Sepsis. Issue 2 (August 2016) - Cirioni, Oscar; Simonetti, Oriana; Pierpaoli, Elisa; Barucca, Alessandra; Ghiselli, Roberto; Orlando, Fiorenza; Pelloni, Maria; Minardi, Daniele; Trombettoni, Maria Michela Cappelletti; Guerrieri, Mario; Offidani, Annamaria; Giacometti, Andrea; et al.
Abstract : ABSTRACT: We investigated the efficacy of colistin combined with pexiganan in experimental mouse models of Acinetobacter baumannii infection. Adult male BALB/c mice received intraperitoneally 1 mL saline containing 2 × 10 10 CFU of susceptible and multiresistant A. baumannii . Two hours after bacterial challenge, animals received 1 mg/kg of colistin, 1 mg/kg of pexiganan, or 1 mg/kg of colistin plus 1 mg/kg of pexiganan. Blood culture positivity, the quantities of bacteria in the intra-abdominal fluid, the rate of lethality and immunological studies, such as immunophenotyping and NK cytotoxicity, were evaluated. In the in vitro study, A. baumannii showed susceptibility to colistin and pexiganan and a strong synergy was observed by testing colistin combined with pexiganan with fractionary inhibitory concentration index of 0.312 for both strains. In the in vivo study colistin or pexiganan alone showed a good antimicrobial efficacy. When colistin was combined with pexiganan, the positive interaction produced low bacterial counts that were statistically significant versus singly treated groups. For both strains the highest rate of survival was observed in combined-treated groups (90%). Pexiganan increased NK cytotoxic activity over the levels of infected and colistin-treated animals. In conclusion, pexiganan combined with colistin was found to be efficacious against A. baumannii infection.